2020
DOI: 10.1097/ajp.0000000000000879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics, and Clinical Course of Neuropathic Pain in Primary Care Patients Consulting With Low Back-related Leg Pain

Abstract: Objectives: Little is known about the epidemiology of neuropathic pain in primary care patients consulting with low back-related leg pain. We aimed to describe prevalence, characteristics, and clinical course of low back-related leg pain patients with and without neuropathic pain, consulting with their family doctor in the United Kingdom. Materials and Methods: This was a prospective cohort study. Data were collected using a standardized baseline clinical examination and self-report questionnaires at baseline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Neuropathic pain affects 20-26.4% of diabetic patients (Bouhassira et al, 2013) and 20% of patients with herpes zoster in the United States (Johnson and Rice, 2014;Saguil et al, 2017). 48-74% patients with low back-related leg pain (Harrisson et al, 2020) and 40% of people after surgery suffer from neuropathic pain (Johansen et al, 2012). Studies have found that about 8.1-17.9% of the Canadian population is affected by neuropathic pain (VanDenKerkhof et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain affects 20-26.4% of diabetic patients (Bouhassira et al, 2013) and 20% of patients with herpes zoster in the United States (Johnson and Rice, 2014;Saguil et al, 2017). 48-74% patients with low back-related leg pain (Harrisson et al, 2020) and 40% of people after surgery suffer from neuropathic pain (Johansen et al, 2012). Studies have found that about 8.1-17.9% of the Canadian population is affected by neuropathic pain (VanDenKerkhof et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions were chosen because they are among the most common pain conditions, could be wellidentified in claims data, and had historically been treated with opioids as the recommended first line therapy prior recent guideline modifications [17]. Individuals were considered to have CNCP only in calendar years in which they met these criteria, due to fluctuations in pain symptoms over time for many chronic pain conditions [30][31][32][33]. We also identified individuals with a cancer diagnosis in each calendar year, excluding skin cancer diagnoses.…”
Section: Plos Onementioning
confidence: 99%
“…Patients with chronic LBP usually present co-occurring pain [2]. In primary care, the prevalence of patients with back-related leg pain varied from 48% to 74% depending on the used description [3]. Sciatica is also known as lumbosacral radiculopathy that presents as a severe form of LBP characterised by radiating leg pain and is considered chronic when symptoms last more than 12 weeks [4].…”
Section: Introductionmentioning
confidence: 99%